Konsep Asnaf Mualaf dan Had Pengukuran Mualaf: Asnaf Mualaf Concept and Mualaf Measurement Limits - Md Ismail, Mohammad Noorazlan; Ali, Nor Aini (Al-Basirah Journal, 2023)
Zakat is seen as one of the social safety net programs to protect people in need, especially muallaf. Muallaf is one of the groups eligible to receive zakat distribution. However, the limitation of the conversion measurement period has implications for the distribution of zakat to this asnaf category. This study presents the concept and limitation of the measurement period of converts in ensuring the social safety net of this group is guaranteed. This study uses library research to collect data. Data findings are analyzed using thematic analysis methods. The results of the study found that asnaf mualaf is dedicated to those who have just converted to Islam as stipulated in the respective State Islamic Religious Administration Enactment. Next, the decision to limit the call period of converts to five years is very appropriate as a measure for them to receive zakat distribution for the category of muallaf.